Sustainability Governance in Islamic Banking: A Bibliometric and Systematic Literature Review of ESG Research - Nurun Najmi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Purpose – ESG (Environmental, Social, and Governance) integration in Islamic banking has attracted growing scholarly attention in recent years. Nevertheless, a comprehensive academic mapping of this rapidly expanding field remains limited. Therefore, the present investigation seeks to conduct a systematic literature review combined with a bibliometric analysis of ESG research in Islamic banking, anchored in currently available observational data. Methodology – This study employs a structured literature review as its primary investigative framework, using the keyword phrases “ESG” and “Islamic bank*” across “Article Titles, Abstracts, and Keywords” in the Scopus database, yielding a collection of 73 documents published between 2020 and 2026. This data extraction took place on August 12, 2026. Subsequently, the gathered information was subjected to a bibliometric examination utilizing the VOSviewer application. Findings – ESG research in Islamic banking remains concentrated in Muslim-majority regions, with prior studies largely centered on Indonesia and Malaysia, alongside GCC countries. Future research should expand toward non-Muslim-majority regions and explore how Shariah-compliant ESG frameworks can inform sustainable finance globally. Beyond bibliometric findings that emphasize governance, sustainability reporting, and profitability themes, this study advances theoretical understanding by positioning ESG disclosure as a strategic instrument for risk mitigation and financial performance enhancement in Islamic banks. In practice, the proposed framework provides guidance for Islamic banking institutions to embed ESG principles consistently with Maqasid al-Shariah objectives. Originality – Research on ESG in Islamic banking is expanding rapidly. However, studies examining the conceptual alignment between ESG frameworks and Shariah principles, and their impact on bank performance dimensions, remain limited.